KEANEKARAGAMAN JENIS SATWALIAR DI KAWASAN PERKEBUNAN KELAPA SAWIT DAN STATUS PERLINDUNGANNYA: STUDI KASUS DI KAWASAN UNIT PENGELOLAAN PT. AGRO KARYA PRIMA LESTARI - Harnios Arief; Yanuar Wicaksono; Domi Suryadi (Media Konservasi, 2010)
Degradation of ecosystems in the region of Agro Karya Prima Lestari Ltd causing this region un function well as wildlife habitat. This is indicated by the low level of wildlife encounters, both on observations during this study took place as well as from interviews with  some of  the people who live in the area. Based on the results of  field  observations  during  the course of  the study, it is known there are 19 species of mammals, 47 species of birds and 5 species of reptiles. Based on the results of  the analysis, it is known that this area contains 10 species of mammals, 16 species of birds and four species of reptiles that includes the category of rare / protected. Keywords: ecosystem, habitat, wildlife, and wildlife species diversity.